Pengaruh Kepemimpinan Kepala Sekolah dan Kinerja Guru Terhadap Mutu Pendidikan Studi di SMKN 2 dan SMAN 2 Kota Serang - Agus Eka Saparudin; H. E. Syarifuddin; Anis Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The background of this research is that to improve the quality of education, it is necessary for a principal who really has the elements contained in a leader in carrying out his duties and functions as well as the role of the teacher in realizing his vision and mission in improving the quality of education in schools. The research was conducted at SMKN 2 and SMAN 2 Serang City. The method used in this research is quantitative method with correlational and verificative techniques. The research method used for data collection is a questionnaire. The results of the study found: First, there is a significant relationship between the influence of principal's leadership on the quality of education by 62%. Second, there is a significant relationship between teacher performance and education quality by 57%. Third, the influence of principals' leadership and teacher performance has a significant relationship to the quality of education by 65.3%.